Silicon carbide powder and method for producing compact

JP7640426B2Active Publication Date: 2025-03-05FUJIMI INCORPORATED
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021161768
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-30
Publication Date
2025-03-05
Estimated Expiration
2041-09-30

AI Technical Summary

Benefits of technology

【0006】 本発明によれば、成形体強度を向上させることが可能な炭化ケイ素粉末、及び成形体の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640426000004
    Figure 0007640426000004
  • Figure 0007640426000001
    Figure 0007640426000001
  • Figure 0007640426000002
    Figure 0007640426000002
Patent Text Reader

Abstract

To provide silicon carbide powder capable of improving the strength of a molded product, and a method for producing the molded product.SOLUTION: A silicon carbide powder contains silicon carbide granules with a specific surface area of 0.26 m2 / g or more, a tap bulk density of 1.3 g / mL or less and a Hausner ratio of 1.3 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silicon carbide powder and a method for producing a molded body using the same. [Background technology]

[0002] Silicon carbide (SiC) has a small thermal expansion coefficient and high mechanical properties (hardness and rigidity), and is therefore used in a variety of applications, such as a reinforcing material for metal matrix composites (MMCs), catalyst carriers, and various filters (see, for example, Patent Documents 1 to 3). In the above applications, porous bodies may be manufactured using SiC powder. For example, one of the manufacturing methods for MMC is the metal infiltration method. The metal infiltration method is a technique in which a ceramic reinforcing material (e.g., SiC) is molded in advance to manufacture a porous body called a preform, and the manufactured preform is infiltrated with molten metal such as aluminum (Al) or silicon (Si). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-124124 A [Patent Document 2] JP 2000-288714 A [Patent Document 3] JP 2013-95637 A Summary of the Invention [Problem to be solved by the invention]

[0004] There are cases where a porous molded body made of silicon carbide is required to have improved mechanical strength. An object of the present invention is to provide a silicon carbide powder capable of improving the mechanical strength of a molded body (hereinafter also referred to as molded body strength), and a method for producing the molded body. [Means for solving the problem]

[0005] The silicon carbide powder according to one embodiment of the present invention has a specific surface area of ​​0.26 m 2 / g or more, having a tapped bulk density of 1.3 g / mL or less, and a Hausner ratio of 1.3 or less. In a method for producing a compact according to one aspect of the present invention, pressure is applied to the silicon carbide powder to form a compact. Effect of the Invention

[0006] According to the present invention, it is possible to provide silicon carbide powder capable of improving the strength of a molded body, and a method for producing the molded body. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a SEM image showing the surface of the SiC granules of Examples 1 and 2 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] An embodiment of the present invention will be described in detail. Note that the following embodiment shows an example of the present invention, and the present invention is not limited to this embodiment. In addition, various modifications and improvements can be made to the following embodiment, and such modifications and improvements can also be included in the present invention. The silicon carbide powder (hereinafter, SiC powder) of this embodiment has a specific surface area of ​​0.26 m 2 The specific surface area of ​​the SiC granules can be measured by, for example, the BET method. The SiC powder of this embodiment has a specific surface area of ​​0.26 m 2 / g or more, has a tapped bulk density of 1.3 g / mL or less, and a Hausner ratio of 1.3 or less. The SiC granules are porous spherical particles with a large specific surface area and many voids (pores).

[0009] The SiC granules of this embodiment are secondary particles granulated from primary particles of SiC. The primary particles are, for example, silicon carbide particles having an α-type crystal system. The SiC granules can be produced by granulating and sintering a powder containing primary particles of SiC. The powder containing primary particles of SiC may be composed of only primary particles of SiC, or may be composed of primary particles of SiC and particles of other components such as additives. Examples of additives include sintering aids and binders for granulation.

[0010] In the SiC powder of this embodiment, the SiC granules are porous spherical particles with a large specific surface area and many voids, so there are many contact points between the SiC granules, and the powder has excellent moldability and molded body strength. For example, the SiC powder of this embodiment can be molded into a molded body by applying pressure. Since there are many contact points between the SiC granules, it is possible to mold a molded body that has high molded body strength and is resistant to deformation, even without adding a binder to the SiC powder. In addition, a binder may be added to the SiC powder of the present embodiment to form a compact. This can further increase the strength of the compact. In addition, additives other than the binder may be added to the SiC powder to form a compact.

[0011] The SiC powder of this embodiment can be used for a variety of applications, such as a reinforcing material for metal matrix composites (MMCs), a catalyst carrier, and various filters. For example, a porous molded body called a preform is used in the metal infiltration method, which is one of the methods for manufacturing MMCs, and this preform may be manufactured using the SiC powder of this embodiment. This makes it possible to manufacture a preform with high molded body strength.

[0012] The SiC powder and compact of this embodiment will be described in further detail below. (Primary particle size) The average particle diameter (D50) of the primary particles (raw material particles) of SiC is not particularly limited, but is preferably 5 μm or more, and more preferably 6 μm or more. The average particle diameter of the primary particles is preferably 12 μm or less, and more preferably 10 μm or less. The average particle diameter (D50) of the primary particles means a particle diameter at which the cumulative frequency from the small particle side is 50% in the cumulative particle diameter distribution based on the volume of the powder containing the primary particles. Hereinafter, the average particle diameter (D50) of the primary particles is also simply referred to as "primary particle diameter (D50)". If the primary particle size (D50) is less than 5 μm, the secondary particles (SiC granules) of the sintered body may be too dense. On the other hand, if the primary particle size (D50) is greater than 12 μm, granulation may become difficult, and it may be difficult to obtain secondary particles of the sintered body. The primary particle size (D50) can be measured, for example, by a laser diffraction / scattering method.

[0013] (secondary particle size) The average particle diameter (D50) of the secondary particles (SiC granules) of SiC is not particularly limited, but is preferably 30 μm or more, and more preferably 34 μm or more. The average particle diameter (D50) of the secondary particles is preferably 60 μm or less, and more preferably 45 μm or less. The average particle diameter (D50) of the secondary particles means a particle diameter where the cumulative frequency from the small particle side is 50% in the cumulative particle diameter distribution based on the volume of the powder containing the secondary particles. Hereinafter, the average particle diameter (D50) of the secondary particles is also simply referred to as "secondary particle diameter (D50)".

[0014] If the secondary particle diameter (D50) is less than 30 μm, the adhesion between the secondary particles will be strong, and the fluidity of the SiC powder will decrease due to aggregation, which may result in poor handling of the SiC powder during molding, for example. Also, when forming a preform used in the metal infiltration method of MMC, the gaps formed in the preform will become locally small, which may make it difficult for molten metal such as aluminum (Al) to penetrate. On the other hand, if the secondary particle diameter (D50) is greater than 60 μm, there may be insufficient contact points between the secondary particles, which may make it difficult to produce a preform used in the metal infiltration method of MMC, for example.

[0015] (particle size ratio) The ratio of the secondary particle diameter (D50) to the primary particle diameter (D50) of SiC (i.e., secondary particle diameter / primary particle diameter) is 30 or less, and more preferably 10 or less. By making the ratio of the secondary particle diameter (D50) to the primary particle diameter (D50) 30 or less, it becomes easy to form large voids in the secondary particles (SiC granules). This makes it easy to form a preform that is easily permeated with molten metal, for example.

[0016] (specific surface area) The specific surface area of ​​SiC granules, for example, is 0.26 m as measured by the BET method. 2 / g or more. The specific surface area of ​​the SiC granules is 0.26 m 2 If the specific surface area of ​​the SiC granules is less than 0.26 m / g, there is a possibility that it will be difficult to produce a preform with high mechanical strength due to insufficient contact between the SiC granules. 2 If the SiC grain size is 1 / g or more, the number of contact points between the SiC grains can be increased, making it easier to produce a preform with high mechanical strength.

[0017] (tap bulk density, Hausner ratio) The tapped bulk density of the SiC powder is 1.3 g / mL or less, preferably 1.1 g / mL or less. If the tapped bulk density is low, it is suggested that voids are formed in the SiC granules. For example, if the tapped bulk density of the SiC powder is 1.3 g / mL or less and the secondary particle diameter (D50) of the SiC granules is 30 μm or more and 60 μm or less, it is suggested that voids of the same size as the gaps between the SiC granules in the SiC powder after tapping are formed in the SiC granules. The Hausner ratio of the SiC powder is 1.3 or less, preferably 1.25. The Hausner ratio is the ratio of the tapped bulk density to the loose bulk density (i.e., tapped bulk density / loose bulk density). If the Hausner ratio is low, the SiC powder has high fluidity and is easy to handle.

[0018] The loose bulk density is the density when a powder is allowed to fall naturally into a container of a certain volume until it is filled to capacity, and the container volume is taken as the powder volume. The loose bulk density can be measured based on the JIS-R-1628 standard. A metal container is used as the measurement container, and the powder is allowed to fall naturally until the container is full. The powder that protrudes from the top of the container is scraped off with a board, and the powder mass is measured and divided by the container volume to calculate the loose bulk density.

[0019] The tapped bulk density is the bulk density when the powder is filled in a container and then mechanically tapped to crush the gaps between the particles and pack them tightly. The tapped bulk density is calculated by mechanically tapping a powder sample into a measurement container, measuring the powder mass and powder volume after tapping until almost no change in the powder volume is observed, and dividing the powder mass by the powder volume. Mechanical tapping is performed by lifting the container and dropping it a specified distance under its own weight. In order to minimize the separation of lumps that occurs during tapping, it is recommended that the container be rotated during tapping.

[0020] (Manufacturing method of SiC powder) The method for producing SiC powder is not particularly limited, but may include a step of producing secondary particles of SiC (SiC granules) by granulating and sintering powder containing primary particles of SiC. The granulation method is not particularly limited, and any known granulation method can be adopted. For example, one or more of the following methods can be adopted: rolling granulation method, fluidized bed granulation method, stirring granulation method, compression granulation method, extrusion granulation method, crushing granulation method, spray drying method, etc. The spray drying method is preferable. In addition, in the manufacturing process of SiC granules, a binder, a sintering aid, etc. may be mixed in addition to the primary particles of SiC.

[0021] For sintering the granulated particles, a general batch type sintering furnace, a continuous type sintering furnace, etc. can be used without any particular limitation. In addition, the sintering conditions such as temperature and time can be appropriately set depending on, for example, the binder and sintering aid used together with the primary particles. When a binder is used, it is preferable to hold the temperature at which the binder can be removed for a certain period of time, and then sinter at a higher temperature, for example, a temperature of 1600°C or higher. The temperature at which the binder can be removed is, for example, 500°C or higher. In addition, when a binder is not used, degreasing at a temperature of, for example, 1000°C or lower is not necessary, and the sintering temperature can be appropriately set so that the granules have the desired strength after sintering. The method for producing the SiC powder may further include a step of crushing the granulated and sintered SiC secondary particles and a step of classifying the particles. These steps can be carried out by using known methods.

[0022] (binder) In this embodiment, a binder may be used when granulating secondary particles (SiC granules) from primary particles of SiC. A binder may also be used when forming a compact from SiC powder, which is an aggregate of SiC granules. Examples of the binder include thermoplastic resins and thermosetting resins. Examples of the thermoplastic resin include polyvinyl alcohol, polyvinylpyrrolidone, acrylonitrile-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, isobutylene-maleic anhydride copolymer, acrylic resin, polycarbonate, polyamide, etc. Examples of the thermosetting resin include epoxy resin, phenol resin, melamine resin, unsaturated polyester resin, etc.

[0023] (Sintering aid) In this embodiment, a sintering aid may be used in the manufacturing process of the SiC secondary particles (SiC granules). As the sintering aid, an aluminum compound, a rare earth compound, a boron compound, a carbon-based compound, or a combination thereof may be used. Specifically, aluminum oxide, aluminum nitrate hydrate, yttrium oxide, boron, boron carbide, carbon powder, etc. may be used.

[0024] (Molded body) The SiC powder of the present invention can be molded into a molded body by adding additives such as a binder as necessary, filling the molded body with the powder, and applying pressure. The molded body can be dried, fired, or otherwise treated as necessary. This makes it possible to obtain a molded body that is porous and has a large pore size and has high mechanical strength.

[0025] The molded body manufactured using the SiC powder of the present invention is not limited to the above preform, and may be, for example, a catalyst carrier or a filter (DPF), etc. Both the catalyst carrier and the filter (DPF) are desired to have excellent moldability and shape retention, and are porous and have a large pore size, so by manufacturing them using the SiC powder of the present invention, it is possible to improve the characteristics. Specifically, industrial catalysts are used after being molded into desired shapes such as tablets, round grains, monoliths (e.g., honeycomb shapes), and so excellent moldability and shape retention in the molding process are important. It has been confirmed that the molded product of the present invention has superior moldability and shape retention through comparison with the examples and comparative examples described below, and therefore an industrial catalyst having excellent moldability and shape retention can be provided.

[0026] In order to improve catalytic activity, it is useful to increase the dispersion and reaction field of active components (e.g., precious metals), but a catalyst carrier with a high specific surface area is suitable for maintaining the active components in a highly dispersed state and improving their utilization. The molded body of the present invention has a certain specific surface area and is a porous material with a large pore diameter, so it is expected to function excellently as a catalyst carrier. Furthermore, in DPFs, it is desirable to increase the size of the pores to a certain extent, thereby improving gas permeability and reducing pressure loss, thereby improving the efficiency of exhaust gas purification. In catalysts other than DPF, it is also effective to increase the pore size and improve the permeability of fluids or gases in order to improve the treatment speed. Since the molded article of the present invention has a large pore size, it is possible to reduce inhibiting factors such as pressure loss, and it is expected that the processing speed will be improved.

[0027] (Resin composition) The SiC granules of the present invention may be blended with a resin to form a molded body of the resin composition. The type of resin that is the raw material of the resin composition is not particularly limited, and may be plastic, curable resin, rubber, etc., but specific examples include polyacrylic acid, polymethacrylic acid, methyl polyacrylate, methyl polymethacrylate, ethyl polyacrylate, ethyl polymethacrylate, butyl polyacrylate, butyl polymethacrylate, polyethylene, polypropylene, polystyrene, polyester, polyamide, polyimide, polyurethane, polyurea, polycarbonate, etc. These resins may be used alone or in combination of two or more. EXAMPLES

[0028] Next, the present invention will be described more specifically with reference to examples and comparative examples. Example 1 The primary particles of silicon carbide were mixed with a sintering aid to obtain a powder (hereinafter also referred to as raw material powder). The primary particles of silicon carbide contained in the raw material powder were α-type silicon carbide (hereinafter referred to as α-SiC) particles with an average particle diameter (D50) of 8.8 μm. The sintering aid used was aluminum nitrate nonahydrate (Al(NO3)3·9H2O) powder. The amount of sintering aid used was 30 mass% of the amount of α-SiC primary particles used (2.16 mass% as aluminum).

[0029] Next, the primary particles of α-SiC, the sintering aid, and the binder were dispersed in a solvent such as water to obtain a slurry. An isobutylene-maleic anhydride copolymer was used as the binder. The amount of binder used in the slurry was 2 mass%. This slurry was fed to a disk-type spray dryer L-8i manufactured by Okawara Kakoki Co., Ltd. and granulated to obtain a granulated mixture of the primary particles of α-SiC, the sintering aid, and the binder.

[0030] Next, the granulated mixture of the α-SiC primary particles, sintering aid, and binder was sintered in an FVS-R resistance heating sintering furnace manufactured by Fuji Denpa Kogyo Co., Ltd. In this sintering process, first, preliminary sintering was performed to remove the binder under conditions of a nitrogen atmosphere, a sintering temperature of 800°C, and a sintering time of 0.5 hours, and then sintering was performed under conditions of an argon atmosphere, a sintering temperature of 1900°C, and a sintering time of 4 hours. The obtained sintered body may be partially bound, so if it is bound, it is crushed using a high-speed rotary crusher (pin mill). The crushed sintered body is subjected to particle size adjustment using a vibrating sieve. In this way, secondary particles (SiC granules) with an average particle size (D50) of 30 μm to 60 μm are obtained.

[0031] Example 2 The SiC granules of Example 2 were produced in the same manner as in Example 1, except that a slurry was obtained by dispersing primary particles of silicon carbide and a sintering aid in a solvent such as water without using a binder, and that the sintering process was performed. In the sintering process of Example 2, sintering was performed under the conditions of an argon atmosphere, a sintering temperature of 800°C, and a sintering time of 4 hours.

[0032] Comparative Example 1 The SiC granules of Comparative Example 1 were manufactured in the same manner as in Example 1, except that the primary particle size (D50) of α-SiC contained in the raw material powder was set to 0.25 μm, that a binder was not used and the primary particles of α-SiC and a sintering aid were dispersed in a solvent such as water to obtain a slurry, and that the sintering process was not performed. In the sintering process of Comparative Example 1, sintering was performed under the conditions of an argon atmosphere, a sintering temperature of 1800° C., and a sintering time of 4 hours.

[0033] Comparative Example 2 The SiC granules of Comparative Example 2 were produced in the same manner as in Comparative Example 1. The difference between Comparative Example 1 and Comparative Example 2 is the specific surface area of ​​the secondary particles (SiC granules). 2 The secondary particles having a specific surface area of ​​less than 0.2 m 2 / g or more was designated as Comparative Example 2. (Comparative Examples 3 and 4) Crushed α-SiC particles, rather than granules, were prepared as Comparative Examples 3 and 4. Comparative Example 3 used large crushed particles, and Comparative Example 4 used fine crushed particles.

[0034] (Particle size) The secondary particle sizes (D10), (D50), and (D90) of Examples 1 and 2 and Comparative Examples 1 and 2, and the particle sizes (D10), (D50), and (D90) of the pulverized particles of Comparative Examples 3 to 6 were measured using a laser diffraction / scattering type particle size distribution analyzer LA-300 manufactured by Horiba, Ltd. The measurement results are shown in Table 1. The secondary particle diameter (D10) means a particle diameter where the cumulative frequency from the small particle side is 10% in the cumulative particle diameter distribution based on the volume of the powder containing the secondary particles. The secondary particle diameter (D90) means a particle diameter where the cumulative frequency from the small particle side is 90% in the cumulative particle diameter distribution based on the volume of the powder containing the secondary particles. The particle diameters (D10), (D50), and (D90) of the crushed particles mean particle diameters measured in the same manner as the secondary particle diameters (D10), (D50), and (D90).

[0035] (specific surface area) The specific surface areas of the SiC granules of Examples 1 and 2 and Comparative Example 1 were measured using a fully automatic BET specific surface area measuring device Macsorb (registered trademark) manufactured by Mountec Co., Ltd. The results are shown in Table 1. (Low bulk density, tapped bulk density, Hausner ratio) The SiC powders obtained in Examples 1 and 2 and Comparative Examples 1 to 6 were measured for loose bulk density and tapped bulk density using a 30 mL metal container based on the JIS-R-1628 standard. From these measured values, the Hausner ratio (= tapped bulk density / loose bulk density) was calculated. The results are shown in Table 1.

[0036] [Table 1]

[0037] (SEM image) The surfaces of the secondary particles (SiC granules) obtained in Examples 1 and 2 and Comparative Examples 1 and 2 were observed using a scanning electron microscope (SEM) and SEM images were taken. The taken SEM images are shown in Figure 1. As can be seen from the SEM image shown in Figure 1, it was confirmed that the SiC granules in Examples 1 and 2 were porous spherical, whereas the SiC granules in Comparative Examples 1 and 2 were dense spherical. (Strength of molded body without binder) The SiC powders obtained in Examples 1 and 2 and Comparative Examples 1 to 4 were subjected to uniaxial molding at 15 MPa using a φ10 mm die without a binder to produce compacts with a diameter of 10 mm and a thickness of 4 to 8 mm. The results are shown in Table 2.

[0038] [Table 2]

[0039] In Table 2 and Table 3 described later, a circle indicates that a molded product could be produced, a cross indicates that the shape was easily disintegrated after molding, and a minus sign indicates that no measurement value was available. Next, a transparent acrylic plate was placed in the center of the molded body, and metal weights were placed on the acrylic plate in the order of 30.9 g → 285.3 g → 389.6 g → 506.0 g → 1180.9 g, and the weights until the molded body collapsed were evaluated. In Table 2 and Table 3 described later, the load capacity (g) of the molded body means the weight at which the molded body was able to maintain its initial height even partially. The collapse weight (g) of the molded body means the weight when the molded body collapses (i.e., when the initial height of the molded body is completely collapsed). Therefore, the collapse weight is a value larger than the load capacity. As shown in Table 2, the molded body of Example 1 collapsed when a metal weight of 30.9 g was placed on it, but the molded body of Example 2 collapsed when a metal weight of 389.6 g was placed on it.

[0040] In Example 1, the height could not be maintained when a 30.9g metal weight was placed on the molded product, and in Example 2, the height could not be maintained when a 389.6g metal weight was placed on the molded product. However, in both Examples 1 and 2, it was possible to produce molded products, and the molded products were able to maintain their shape without the metal weight placed on them. In Comparative Examples 1 to 4, the molded products were easily disintegrated without the metal weight placed on them. From these results, it was confirmed that, in the absence of a binder, Examples 1 and 2 had superior molded product strength to Comparative Examples 1 to 4.

[0041] (Strength of molded body with binder) A binder was added to the SiC powder obtained in Examples 1 and 2 and Comparative Examples 1 to 4 at a concentration of 10 mass %, and a molded body having a diameter of 10 mm and a thickness of 4 to 8 mm was produced by uniaxial molding at 10 MPa using a φ10 mm mold. The results are shown in Table 3. As shown in Table 3, when a binder was added, a molded body could be produced not only in Examples 1 and 2 but also in Comparative Examples 1 to 4.

[0042] [Table 3]

[0043] Next, a transparent acrylic plate was placed in the center of the molded body, and metal weights were placed on the acrylic plate in the order of 30.9g → 285.3g → 389.6g → 506.0g → 1180.9g, and the weights until the molded body collapsed were evaluated. As shown in Table 3, the molded bodies of Examples 1 and 2 were able to maintain their initial height even when a metal weight of 1180.9g was placed on them. In other words, the load capacity and collapse weight of Examples 1 and 2 were greater than 1180.9g. In contrast, the load-bearing capacity and collapse weight of Comparative Examples 1 to 4 were lower than those of Examples 1 and 2. From these results, it was confirmed that, even in the case where a binder was used, Examples 1 and 2 had superior molded body strength to Comparative Examples 1 to 4.

Claims

1. Specific surface area is 0.26 m 2 / g or more of silicon carbide granules, Silicon carbide powder having a tapped bulk density of 1.3 g / mL or less and a Hausner ratio of 1.3 or less.

2. The silicon carbide powder according to claim 1, wherein the silicon carbide granules have an average particle size (D50) of 30 μm or more and 60 μm or less.

3. The average particle diameter (D50) of the primary particles used in granulation of the silicon carbide granules is defined as the primary particle diameter, and the average particle diameter (D50) of the silicon carbide granules is defined as the secondary particle diameter, 3. The silicon carbide powder according to claim 1, wherein the ratio of the secondary particle size to the primary particle size is 30 or less.

4. The silicon carbide powder according to any one of claims 1 to 3, wherein the primary particles used for granulating the silicon carbide granules are silicon carbide particles having an α-type crystal system.

5. A method for producing a molded body, comprising applying pressure to the silicon carbide powder according to any one of claims 1 to 4 to mold the molded body.

Citation Information

Patent Citations

  • Spherical crystalline silicon carbide powder and method for manufacturing same

    CN104512893A

  • Production of metal-ceramics composite material

    JP2000288714A

  • Hollow granular particle and method for manufacturing the same, and gas treatment device comprising the same

    JP2013071886A

  • Spherical -type silicon carbide, production method thereof, and sintered body or organic resin composite using the silicon carbide as raw material

    JP2013095637A

  • Silicon carbide granule and method for manufacturing the same

    JP2014214058A